The Impact of Financial Literacy on the Choice of Financial Instruments by Private Investors in Russian Conditions - R. М. Melnikov (Финансы: теория и практика, 2024)
The paper examines the impact of financial literacy, risk tolerance and expectations on the choice of financial instruments by private investors using data from the 5th wave of the All-Russian household survey on consumer finance, conducted in 2022 at the request of the Bank of Russia. This is the first time such an analysis using Russian data has been carried out.   The purpose of this study is to determine the role of financial literacy in making individual investment decisions.   The results of logit- and tobit-regression estimation show that the investments of Russian citizens in stocks, bonds and mutual funds are mainly limited by a high degree of financial risk aversion, and not by an insufficient level of financial literacy. Expectations do not affect the choice of financial instruments. The refusal of individuals with low tolerance for possible losses to invest in securities market instruments and the preference for bank deposits is a reasonable and rational decision in case of the absence of deep financial competencies. At the same time, this creates unfavorable conditions for the implementation of the long-term savings program developed by the Ministry of Finance of Russia and attracting long-term investment resources by Russian companies in the real sector of the economy in the context of closed access to global financial markets. The active acquisition of cryptocurrencies by respondents with high self-esteem of their own financial competencies, but low incomes and low financial literacy ratings, calculated on the basis of answers to test tasks, generates increased risks of not achieving financial goals. Therefore, it is necessary to pay special attention to the risks of transactions with cryptocurrencies as a part of the implementation of initiatives promoted by the Moscow State University and the Bank of Russia to improve the level of financial literacy and financial culture of Russian citizens. It is proposed to include questions that allow assessing advanced financial competencies and forming the values of variables that can act as instruments for the level of financial literacy in subsequent waves of the survey to develop the information base for further research.